Constitution of the Rule of rights: reflections on evolutions and setbacks throughout history (Research, Society and Development, 2022)
In this article we aim to reflect on the relationship between the role of the State in society and the control established by the Capitalist Mode of Production in the contemporary world, passing through the conceptual evolution of the State, its liberal democratic form manifested in the field of the right to freedom, soon contained by class interests and contradictorily merged with rights conquered by civil society movements. It takes as its real basis the denial of rights, freedom, the social crisis and the feeling of fear and insecurity that affects people's lives. It starts from the abstract and historical analysis of the State, moving on to the configuration of rights and their denial under neoliberalism, when society produces forms of power and surveillance to obtain legitimacy and control over individuals. We observe that addressing social rights in a historical moment in which hegemony is stronger and more complex has become a great challenge, which requires the search for a new subjectivity to combat capitalism and its forms of imposition of prejudices and social discrimination. and politicians that reinforce the influence of the most reactionary social sectors in our country.